Aesthetic treatment of bruxism (2017)
Bruxism is a diurnal or nocturnal parafunctional activity that includes unconscious clenching, grinding, or bracing of the teeth. An extensive medical history should be taken in these patients so proper diagnosis can be made. Habits such as biting the tongue, cheeks or lips, chewing gum or eating seeds for many hours per day, biting nails, and/or biting hard objects, will cause and/or exacerbate pre-existing bruxism. The etiology of bruxism is uncertain, but it is hypothesized to be associated with genetic, structural, and psychosocial factors. Over time, chronic clenching of the jaw leads to hypertrophy of masseters and temporalis musculature causing the face to take on a masculine and square appearance. Patients commonly present to dermatology cosmetic practices wishing to have a more slim, softer appearing face. This review is the first paper to discuss aesthetic treatment options for complications of bruxism including masseter and temporalis hypertrophy and the associated accelerated aging of the lower face.